Refer to the graph below.
Work Step by Step
Solve for $y$. $2x-y=3 \\2x-y-2x=3-2x \\-y=3-2x \\-y=-2x+3 \\-1(-y)=-1(-2x+3) \\y=2x-3$ This means that the given equation is equivalent to, and has the same graph as, $y=2x-3$. RECALL: The slope-intercept form of a line's equation is $y=mx+b$ where $m$=slope and $(0, b)$ is the line's y-intercept. Thus, the equation $y=2x-3$ has a slope of $2$ and a y-intercept of $(0, -3)$. To graph the given equation, perform the following steps: (1) Plot the y-intercept $(0, -3)$. (2) Use the slope to plot a second point. From $(0, -3)$, move 2 units up (the rise) and 1 unit to the right (the run) to reach $(1, -1)$. Plot $(1, -1)$. (3) Connect the two points using a line to complete the graph. (Refer to the graph in the answer part above.)